Correlation of acute suppurative otitis media with infant feeding position - Regina, M; Radhamani, K V; Sanu, Moideen P; Arun, G N; Mohan, Mogarnad (Indian Journal of Child Health, 2017)
Background: Acute otitis media (AOM) is the most common childhood illness necessitating medical therapy for children younger than 5 years. Long-term and exclusive breastfeeding is associated with protection against AOM. However, faulty feeding position and habits can lead to the occurrence of AOM in infants. Objectives: The aim of this study is to assess the risk of occurrence of AOM with faulty feeding positions during the 1st year of life. Materials and Methods: All breastfed infants <1 year with a provisional diagnosis of AOM, during August 2015 - January 2016 (6 months), were included in the study. Syndromic children, children with craniofacial anomalies, bottle-fed infants, and those not willing to participate in the study were excluded from the study. Demographic details and detailed history, especially, the feeding position were collected from the parents. Diagnosis of AOM was confirmed by a senior ENT surgeon after otoscopic examination. Results: 118 children with AOM were statistically analyzed. They aged between 1 month and 12 months with a mean of 6.8 and standard deviation of 4.1 months. There were 68 (57.62%) males and 50 (42.37%) females. No statistical significance was observed for sex or laterality with AOM. A statistically significant correlation was observed between AOM and age groups, AOM and position of the baby. Conclusion: In this study, we have observed that feeding the infant in supine position significantly increases the risk of AOM in infants.